The Development Of The Legal Framework For Autonomous Shipping: Lessons Learned From A Regulation For A Driverless Car - Roman Dremliuga; Mohd Hazmi Mohd Rusli (Universiti Sains Islam Malaysia, 2024)
Indexed by ERA